An evaluation using micro-CT data of the stress formed in the crown and periodontal tissues from the use of PEEK post and PEEK crown: A 3D finite element analysis study - Tekin, Samet; Adıgüzel, Özkan; Cangul, Suzan (My University, 2018)
Aim: Metal-supported ceramics as crown material and glass fiber posts asdental post materials are in frequent current use. In recent years, it hasbeen claimed that stress-based biomechanical problems in dentistry canbe resolved with the benefit of the low elasticity modulus ofpolyetheretherketone (PEEK) material. The aim of this study was to usefinite element analysis (FEA) to compare the stresses formed by forcesapplied after the use of PEEK material as dental post and crown materialas an alternative to glass fiber posts and metal-supported ceramic crowns.Methodology: The stress analysis method used in this study was FEA.First, micro-computed tomography (micro-CT) images were obtained of amaxillary central incisor tooth and the data of the post materials scannedwith a 3-dimensional (3D) laser scanner were uploaded to a computerprogram. 3D models were obtained with designs made in the computerprogram of all the materials. The modelling of a maxillary central toothwas completed using 2 different post materials (glass fiber and PEEK) and2 different crown materials (metal ceramic and PEEK) and 4 groups wereformed for analysis. By applying force of 100 N at 135ofrom the absolutecentral point of the palatinal surface of the tooth, the stress values anddistribution occurring in the 3D periodontal models were compared.Results: The use of PEEK post reduced the stresses occurring on theperiodontal ligament (PDL) and the cortical bone, and caused no significantchange in the stresses on the crown. The use of PEEK crown reduced thestresses occurring on the crown and increased the stresses occurring on thePDL and cortical bone.Conclusions: With further in vitro and clinical studies of PEEK material,it can be considered that within a short time PEEK post and PEEK crowncould be in routine use in dentistry.
Keywords: Diş Hekimliği